Mutagenic oligonucleotide-directed PCR amplification (Mod-PCR): an efficient method for generating random base substitution mutations in a DNA sequence element. - Chiang, L W; Kovari, I; Howe, M M (Genome Research, 1993)
Saturation mutagenesis is one approach for determining the contributions of individual base pairs to the structure and function of defined DNA sequence elements. In this paper, we describe a novel method for saturation mutagenesis involving PCR amplification with degenerate synthetic oligonucleotides as primers. The degeneracy is confined to a specific target within the primer by mixing a low percentage of the three non-wild type (non-WT) nucleotide precursors with WT at specific positions during primer synthesis. PCR amplification of WT template DNA with the degenerate primer and an opposing WT primer, followed by subsequent cloning using restriction sites designed into the primers, results in recovery of a population of randomly mutated products. Since primers with multiple mutations hybridize less efficiently to WT template DNA during PCR amplification, the recovery of mutants with multiple base changes is greatly reduced. The efficient generation of random point mutations with this method allows the construction of separate mutant populations, each mutagenized over a different portion of the DNA sequence element. If a phenotypic assay is available, these populations can be screened directly to define those regions within the element that are important for activity. Only those populations containing mutations in the important regions require further characterization by DNA sequence analysis.